Effect of storey height on seismic performance of elevated reinforced concrete water tank - Farah Aqila, Tun Riduan (2017)
This research is to study the effect of storey height on the lateral strength of elevated reinforced concrete (RC) water tank due to earthquake. Elevated RC water tank is the most important structure to supply the water demand for users. Therefore, these structures must survive during disaster like earthquake. It must remain functional even after the earthquakes as water tanks are required to provide water for drinking and firefighting purpose. However, seismic design was not concerned by Civil Engineers in Malaysia almost in all of the building. Recently, few earthquake start occurring in few regions in Malaysia and neighboring country like Indonesia and Philippines. The tremors occur in this neighboring country affect the reinforced concrete structure in Malaysia which the structural in Malaysia are not design to resist seismic loading. The objective of this study is to model and analyses the effect of storey height on the lateral strength of elevated RC water tank and to investigate the effect of storey height on the interstorey drift ratio of elevated RC water tank. Method that been used in this work is the pushover analysis (POA) using SAP 2000 software. POA is the one of the method that been used for seismic performance evaluation of structures. Two basic models of elevated RC water tank which have four and seven storeys has been used for this project. These two models are designed repeatedly with different storey height. All models are designed based on BS8110 to represent the existing elevated RC water tank. The results of the POA give a capacity curve in form of base shear force versus top storey displacement. From the result, this study conclude that model with shorter column height tend to have higher base shear force compared to model with longer column height.